2021
DOI: 10.3390/antibiotics10030313
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Similar Mcr-1 Carrying Plasmids among Different Escherichia coli Lineages Isolated from Livestock and the Farmer

Abstract: Colistin use has mostly been stopped in human medicine, due to its toxicity. However, nowadays, it still is used as a last-resort antibiotic to treat hospital infections caused by multi-drug resistant Enterobacteriaceae. On the contrary, colistin has been used in veterinary medicine until recently. In this study, 210 fecal samples from pigs (n = 57), calves (n = 152), and the farmer (n = 1) were collected from a farm where E. coli harboring mcr-1–mcr-3 was previously detected. Samples were plated, and mcr-gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 62 publications
(43 reference statements)
3
22
0
1
Order By: Relevance
“…In the central area of Thailand, the antimicrobials that are mainly used are colistin, cephalosporins, tiamulin, amoxicillin, tilmicosin, aminoglycosides (gentamycin), and oxytetracycline ( 50 ). The use of other antimicrobials during the production cycle of pigs could co-select for colistin resistance ( 51 , 52 ). Resistances to other potential agents like heavy metals or biocides that may be linked with antibiotics resistance genes also are a matter for concern.…”
Section: Discussionmentioning
confidence: 99%
“…In the central area of Thailand, the antimicrobials that are mainly used are colistin, cephalosporins, tiamulin, amoxicillin, tilmicosin, aminoglycosides (gentamycin), and oxytetracycline ( 50 ). The use of other antimicrobials during the production cycle of pigs could co-select for colistin resistance ( 51 , 52 ). Resistances to other potential agents like heavy metals or biocides that may be linked with antibiotics resistance genes also are a matter for concern.…”
Section: Discussionmentioning
confidence: 99%
“… Vines et al (2021) collected 210 fecal samples from farm animals and the farmer and analyzed the spread of mcr -associated with plasmids among E. coli by multiplex PCR. It was identified 18 colistin-resistant E. coli isolates carrying mcr -1 (including 13 from calves, four from pigs, and one from the farmer, respectively) and 33 virulence factors.…”
Section: Potential Risks Of Antibiotic Resistance In Food Animal Farmsmentioning
confidence: 99%
“…It was identified 18 colistin-resistant E. coli isolates carrying mcr -1 (including 13 from calves, four from pigs, and one from the farmer, respectively) and 33 virulence factors. Moreover, the mcr -1 gene was transferred from the calf to the farmer, posing the risk of a farm as a reservoir of ARB with zoonotic potential ( Vines et al, 2021 ).…”
Section: Potential Risks Of Antibiotic Resistance In Food Animal Farmsmentioning
confidence: 99%
“…It is known the ability of the mcr cassette to jump into several types of plasmids, including the IncX4 plasmid, which seems to be one of the predominant replicon types of plasmids, carrying the mcr-1 gene [ 15 ]. Moreover, the possibility of the transmission of mcr -positive IncX4 plasmids among different bacterial species, and from animals to humans or vice versa, has been documented, as reported elsewhere [ 37 ]. The WGS revealed that all six isolates carried blaCTX-M1 , tet(A) , dfrA1 and sul1 genes, mediating cefotaxime, tetracycline, trimethoprim and sulfonamide resistance, respectively.…”
Section: Discussionmentioning
confidence: 74%